Analysis of 9 Cases of Takotsubo Syndrome and an Analysis of the Clinical Characteristics of Takotsubo Syndrome From a Chinese Population - Yan, Ju; Madina, Mahesutihan; Deng, Changjiang; Yuan, Qianru; Cao, Shixiong; Xie, Xiang; Ma, Yitong (Frontiers in Cardiovascular Medicine, 2021)
Objective: To summarize the clinical features, hematology and imaging features of Takotsubo syndrome. Methods: The hospitalization data of Takotsubo syndrome patients in the First Affiliated Hospital of Xinjiang Medical University from January 2015 to December 2020 were collected, and their clinical characteristics were summarized. Patient outcomes were clarified through follow-up visits, and relevant objective indicators were statistically analyzed before and after admission. The characteristics of TTS incidence in Chinese population were summarized by searching three（Wanfang、CNKI、China,s VIP database）major databases in China（ PRISMA）.Results: A total of 9 patients were enrolled, including 6 females (66.7%). The mean age of onset was 46.4 years old, the median time from onset to treatment was 1 day. The main symptom of 8 cases (88.9%) was chest pain, 1 case had a main symptom of syncope, and 7 cases (77.8%) had mood fluctuations or mental stimulation as the main symptom of the disease. Paired T tests were conducted on routine blood, biochemical, coagulation, myocardial markers, inflammatory indicators and objective indicators of ECG before and after admission. The study found that the counts of white blood cells and neutrophils were statistically significant (P < 0.05). Prolongation of the QT interval was observed in all 9 patients. After a mean follow-up of 24±28 months, no adverse cardiovascular events or recurrence occurred. Conclusion: Takotsubo syndrome is a group of clinical syndromes with emotional or somatic stimulation and chest pain as the main symptoms, partly accompanied by an increase in white blood cells, neutrophilic granulocyte count, creatine kinase, and troponin and is characterized by a prolonged QT interval and no obvious coronary stenosis. The prognosis is generally good, with few serious complications.